Synthesis of raspberry ketone using aluminium bentonite catalyst - Patange, Rutuja S.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Flavour and Fragrance Journal, 2026)
In this study, Raspberry ketone is synthesized from phenol and 4-hydroxy-2-butanone using metal-exchanged bentonite catalysts. Catalysts such as Al/bentonite, Fe/bentonite, Zn/bentonite, and Zr/bentonite were utilized, where Al/bentonite exhibited the highest conversion of 4-hydroxy-2-butanone, 99% with 70% selectivity for Raspberry ketone. The excellent activity was observed due to the high acidity of Al/bentonite compared to the other metal-exchanged catalysts. Different reaction parameters, such as temperature, time, molar ratio, and catalyst reusability, were studied. The catalyst characterization was performed using XPS, N2-adsorption-desorption, and FTIR analysis. The use of a heterogeneous catalyst provides a cost-effective and environmentally friendly approach to the production of raspberry ketone.
Keywords: 4-hydroxy-2-butanone; Al/bentonite; phenol; raspberry ketone